CCK-2/Gastrin-R Immunodistribution in a Solid Pseudopapillary Pancreatic Tumor: A Case Report of a 28-Years-Old North African Woman - Sellam, Feriel; Harir, Noria; Mrabent, Nesrine M; Tou, Abdenacer; Belkralladi, Houria; Salah, Rachida; Zeggai, Soumia (Global Journal of Medical and Clinical Case Reports, 2016)
<p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The presence of a large bulky pancreatic tumour in a young female should raise suspicions of the diagnosis of solid-pseduopapillary tumour of the pancreas. <p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Solid pseudopapillary neoplasms of the pancreas are uncommon, accounting for only 1-2% of all pancreatic neoplasms. These tumors are being detected at an increased rate, probably due to the increased awareness and the liberal use of imaging. <p style="box-sizing: border-box; outline: none; margin: 0px 0px 15px; padding: 0px; border: 0px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-weight: 400; font-stretch: inherit; line-height: 25px; font-family: Roboto, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-size: 15px; color: #222222; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">We report a case of a 28-year-old North African woman with no prior medical or surgical history diagnosed with solid pseudopapillary pancreatic tumor. Our immunohistochemical study demonstrated that the tumor cells were positive for CCK-2/gastrin receptors and that were highly expressed within the cytoplasmic area of the cells. Hence we attempted to raise a hypothesis and to establish a link between some female hormones which represents powerful regulators of the expression of CCK and their possible impact on the development of solid pseudopapillary pancreatic tumours in young women.